KORELASI ANTARA KEBIASAAN MEMBACA DENGAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS X SMA NEGERI 16 MERANGIN - zamdani zamdani (LP3M STKIP Muhammadiyah Muara Bungo, 2022)
This study aims to (1) describe the level of reading habits of class X students of SMA Negeri 16 Merangin; (2) describe the level of learning outcomes Indonesian class X students of SMA Negeri 16 Merangin; and (3) explain the relationship between reading habits and learning outcomes Indonesian class X students of SMA Negeri 16 Merangin. The results of learning Bahasa Indonesia, class X students of SMA Negeri 16 Merangin are influenced by many factors, including reading habits. So a study was conducted to describe the relationship between reading habits and learning outcomes Indonesian. This study uses a correlational quantitative method by connecting two variables, namely reading habit variables as free variables, and learning outcomes Indonesian as bound variables. The solution and the sample of this study were class X students of SMA Negeri 16 for Merangin, totaling 40 people. Data were collected using likert scale questionnaires for reading habits and documentation techniques to obtain data on learning outcomes Indonesian, through daily test value documentation. The results of the data analysis showed that the value of the correlation coefficient of variable X to variable Y was 6.16 >T tubel or 6.16 > 1.684 then Ha was accepted and Ho was rejected. The conclusion of this study is that there is a significant relationship between reading habits and learning outcomes Indonesian class X SMA Negeri 16 Merangin students.